Pemahaman Kausalitas Dalam Konteks Kasus Kopi Sianida Jessica Wongso: Pendekatan Multidisiplin - Anbiyaa, Fajri; Purnomo, Hadi (CT. Rajawali media Utama, 2024)
The case of cyanide-contaminated coffee involving Jessica Wongso in 2016 raised concerns and deep questions about the understanding of causality in Indonesian society. While the legal approach focused on proving that Jessica intentionally added cyanide to Mirna Salihin's coffee, the causality aspects in this case are complex and involve multidisciplinary sciences. Issues such as Jessica's motives, peculiarities in her actions, and claims that Mirna was not actually poisoned sparked public debates. Causality understanding was strengthened by forensic, toxicological, and psychological evidence, necessitating a multidisciplinary approach to combine legal, forensic, psychological, toxicological, and sociological perspectives. This research aims to comprehend causality in the context of this case from various angles for a more comprehensive understanding. The qualitative method was employed, utilizing theories of causality, forensic, and criminal psychology.The results, based on Article 340 of the Criminal Code regarding premeditated murder, showed that the legal approach required proving Jessica's intent to kill, planning the use of cyanide in coffee, and administering it to Mirna. Causality in the legal context involves the cause-and-effect relationship between Jessica's actions and Mirna's death, proven through autopsy results, forensic analysis, and witness testimonies. Toxicological and forensic medicine approaches ensured the scientific validity of evidence, while psychological and sociological perspectives provided insights into motives and the social context of the case. Consequently, in October 2016, Jessica Wongso was sentenced to 20 years in prison for premeditated murder, a decision upheld by the Jakarta High Court in April 2017.